Kontribusi Teater Kampus dalam Pendidikan Karakter Mahasiswa: Studi Kasus Teater Lingkar Fakultas Ilmu Budaya Universitas Brawijaya - Fredy Nugroho Setiawan; Yusri Fajar (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2017)
The study aims to explain the contribution of “Teater Lingkar” of Faculty of Cultural Studies Universitas Brawijaya in educating its members’ characters. The researcher employs qualitative method in collecting and recording data by applying the principles of field research in interviewing informants and library research in gathering textual and visual data. The analysis of the interview reveals that “Teater Lingkar” has contributed in improving the character quality of its members. In this case, the group serves as a medium of character education that helps its members to have better personality. It is obtained through activities they have done in the group. Thus, this finding provides an example of the significance of theater groups on campus in terms of their contribution in educating and improving the quality of their members’ characters.